Systematic Literature Review: Delone and Mclean Model using VOSViewer on Google Scholar Database Case Year 2010-2020 - Dhian Nur Rahayu; Lila Setiyani (International Journal of Science, Technology & Management, 2022)
This study aims to examine the development of the Delone and Mclean information system success model. This research was conducted to determine: (1) a map of the development of the number of publications on the Delone and Mclean model; (2) find out which scientific articles have the highest number of citations; (3) knowing the development map of scientific publications based on keywords. The data sources used in this study are scientific articles in the Google Scholar database with the keywords Delone and Mclean, with the categories article title, abstract, keywords in the 2016-2020 range. The search results show that there are 270 scientific articles that match the keywords based on the Harzing's Publish or Perish application. The results showed that the development of the Delone and Mclean model in 2010 - 2020 which was the highest in the Google Scholar database occurred in 2020 which reached 68 publications or 25%. Meanwhile, the publications that have the highest number of citations are Nils Urbach and Benjamin Müller (2016) which were quoted 379 times. The development map of scientific publications based on the keywords delone and mclean analyzed using the VOSViewer application shows that the development map of the delone and mclean model is divided into 4 clusters. The red cluster 1 consists of 14 items, the green cluster 2 consists of 11 items, the blue cluster 3 consists of 10 items, and the yellow cluster 4 consists of 6 items.